Curried Keynesianism meets the master: Lauchlin Currie's memorandum on The General Theory for the Federal Reserve Board. (January 2016) - Vernengo, Matías
Abstract : This short paper introduces Lauchlin Currie's unpublished memorandum to the Board of Governors of the Federal Reserve discussing Keynes's General Theory . The memorandum falls short of a full review of Keynes's magnum opus, but together with other published material it provides a picture of Keynesian ideas within the Fed during the Great Depression. It is suggested that Currie's views on Keynes are relevant, in particular because, contrary to what would become the dominant view, he does not think that wage or interest-rate rigidity is at the heart of the Keynesian results.